The Association between Intradialytic Hypertension and Metabolic Disorders in End Stage Renal Disease - Vaia D. Raikou; Despina Kyriaki (International Journal of Hypertension)
Background. Intradialytic hypertension was associated with a high mortality risk. We examined the relationship between intradialytic hypertension and metabolic disorders in hemodialysis treatment patients. Methods. We studied 76 patients in online hemodiafiltration. Dialysis adequacy was defined by Kt/V for urea. Normalized protein catabolic rate (nPCR), as a marker of protein intake, was calculated. Sodium removal was determined as percent sodium removal. Metabolic acidosis was determined by serum bicarbonate less than 22 mmol/L. Interdialytic urine volume more than 100 ml was recorded. Intradialytic hypertension was defined by an increase in systolic blood pressure equal to 10 mmHg from pre- to posthemodialysis. Arterial stiffness was assessed as carotid-femoral pulse wave velocity (c-fPWV) and carotid augmentation index (AIx). Chi-square tests and logistic regression analysis were applied for intradialytic hypertension prediction. Results. Patients with intradialytic hypertension were older and had significantly lower hemoglobin, nPCR, urine output, and serum bicarbonate and significantly higher c-fPWV, though similar Kt/V for urea, than patients without intradialytic hypertension. They also had increased sodium removal and pulse pressure related to less urine output. Serum bicarbonate was inversely associated with c-fPWV (r=-0.377, p=0.001). Chi-square test showed significant association between intradialytic hypertension and serum bicarbonate < 22 mmol/L (x2=5.6, p=0.01), which was supported by an adjusted model. Conclusion. The intradialytic hypertension was significantly associated with metabolic disorders including malnutrition/inflammation and uncontrolled metabolic acidosis in hemodialysis treatment patients. Severe metabolic acidosis may reflect sodium imbalance and hemodynamic instability of these patients resulting in volume overload and increased vascular resistance.